Comparison of heritability estimates from time series and least squares adjustments in Murrah buffaloes - WAKCHAURE, R S; SACHDEVA, G K; GANDHI, R S (The Indian Journal of Animal Sciences, 2011)
The data on 1200 fIrst lactation records of Murrah buffaloes spread over a period of 36 years (1970-2005) were analyzed by least squares and time series analyses for ascertaining correction factors to adjust the data for non-geneic factors to estimate heritability of first lactation traits. The traits considered were age at first calving (AFC), first lactation 305- day or less yield (FL305DMY), first lactation total milk yield (FLTMY), first lactation length (FLL), first service period (FSP), first dry period (FDP) and first calving interval (FCl). The data were adjusted for significant non-genetic factors to estimate heritability from all the 4 sets. Higher heritabilities of AFC. FL305DMY and FLL were estimated from least squares adjustments. However, the estimate of heritability of FLTMY was higher from the time series adjustments. The heritability estimates of reproduction traits from the data adjusted by both the correction factors were not significantly different from zero. It was concluded that time series adjustments were not more effective to adjust the data for non-genetic factors in Murrah buffaloes.Â